Optimization of Vanadium Content for Achieving Higher Wear Resistance and Hardness in High Cr-V White Cast Irons for Ball Tube Mill Liner Application (Fracture and Structural Integrity, 2019)
The liner materials, being used, at present from high Cr cast iron grades in coal fired tube mills are less promising due to lower combination of abrasion wear resistance, hardness and impact toughness properties, thus giving life of only 25,000 to 35,000 hours. In this study, focus was given to develop a high Cr-V cast iron of high abrasion wear resistance with higher hardness and impact strength for ball tube mill liner application. The developed liner possesses high abrasive wear resistance and impact resistance simultaneously for having life of 40,000 to 50,000 hours. This grade was made using induction melting and sand casting method. The casting was heat treated in two stages to achieve higher abrasion wear resistance and mechanical properties. Various tests like chemical analysis, abrasion wear, hardness and impact tests were conducted on the above developed material. Abrasion wear test results show a low wear loss value (2.7 to 4.4 mg/min). Hardness and impact tests show a high combination of hardness (57 to 64 HRC) and impact strength (44 to 57 J/cm2). Prototype tube mill liners were manufactured and tested in a tube mill at 250MW site. Results obtained from site testing are also discussed in this study.
Keywords: High Cr cast iron; High Cr-V cast iron; Abrasion wear; Hardness; Impact strength